Persian Linguistic and Rhetorical Pathology in The Telegram Communication Network - M. Hedayat Mofidi; A. Kamyabigol; A. Alizadeh (Taḥqīqāt-i Farhangī-i Īrān)
Today, the mobile phone, with its wide range of features, is an inexpensive, easy to use, and most modern communication tool. One of the special applications of smart phones is providing spaces and facilities such as SMS services, virtual networks, and interactive groups that link people and groups from different linguistic and cultural background. In this paper, we tried to study the messages of the Farsi-speaking users of the Telegram communication network from the linguistics perspective. In this regard, the linguistics and rhetorical correspondence of short messages in Persian language was studied by the content-analysis method. The statistical population consisted of 150 messages which contained 327 sentences. These messages were randomly selected from 5 different groups. Persian language used in cyberspace differs from standard Persian language. The first step in correcting communication language errors in cyberspace is to inform the users about the type of errors.